Ignoring Respect: The Effects of Threat to Face on Replies and the Ensuing Questions During Broadcast Political Interviews in Japan. (October 2019) - Feldman, Ofer; Kinoshita, Ken
This article examines the effect of threat to face to both interviewers and interviewees during live televised interview programs in Japan, where the concept of "face" is of extreme importance in maintaining interpersonal relationships. Based on 2, 422 questions identified during 120 interviews broadcast over a period of 12 months on four television programs, the goal is twofold: First, to assess the extent to which questions that contain a certain level of threat to face affect the interviewees' replies, and second, to measure the extent to which interviewees' replies affect the interviewers' subsequent questions. The findings indicate that questions containing a higher degree of threat to the interviewers' face resulted in less clear and comprehensible replies. Furthermore, equivocal responses to questions increased the chance of a follow-up question being more face-threatening, suggesting that interviewers who are unsatisfied with the replies of their interviewees manifest their displeasure with tougher follow-up questions.